HUBUNGAN PENGETAHUAN DENGAN KEAKTIFAN KADER POSYANDU DALAM PENYUSUNAN PELAPORAN ADMINISTRASI KESEHATAN - Nurul Fatimah; Anindita Hasniati Rahmah; Widya Kaharani Putri (Jurnal Kesehatan, 2023)
Posyandu is one of the community-based health initiatives managed and implemented by the community members themselves, aimed at supporting healthcare development. Its primary objective is to empower the community and facilitate their access to basic healthcare services. The success of Posyandu's health administration greatly depends on the roles played by its cadre members, who are the backbone of all activities conducted within Posyandu. However, in practice, not all cadre members are actively involved in carrying out their responsibilities in health administration reporting within Posyandu activities. This study aims to investigate the relationship between the level of knowledge possessed by cadre members and their level of involvement in Posyandu activities. Methodology: This research utilizes an analytical survey approach with a cross-sectional design. The sample selection technique involves total sampling, encompassing all 130 Posyandu cadre members located in the research area of UPT within the Gabus I Pati Health Center. Data analysis employs both univariate and bivariate analyses, including the chi-square test. Results: The chi-square test results indicate a pvalue of 0.002, signifying a significant relationship between knowledge and the level of cadre members' involvement in Posyandu activities within the working area of UPT Gabus I Pati Health Center. Conclusion: In conclusion, there is a significant correlation between the level of health administration knowledge possessed by cadre members and their level of activity in preparing health administration reports within Posyandu activities. Therefore, several recommendations can be proposed, including regular mentoring by healthcare professionals in the local Puskesmas area, organizing periodic training for cadre members on health administration and Posyandu-related topics, and local government attention to the welfare of cadre members as efforts to boost their motivation in fulfilling their Posyandu duties. Keywords: Knowledge, Cadre Activity, Health Administration